Quantitative analysis of single‐nucleotide polymorphisms by pyrosequencing with di‐base addition. Issue 6 (1st February 2017) - Pu, Dan; Pan, Rongfang; Liu, Wenbin; Xiao, Pengfeng
Abstract : We have developed and validated a novel method for quantitative detection of SNPs by using pyrosequencing with di‐base addition (PDBA). Based on the principle that the signal intensity is proportional to the template concentration within a linear concentration range, linear formula ( Y = AX + B ) for each genotype is established, and the relationship between two genotypes of a single SNP can be resolved by corresponding linear formulas. Here, PDBA assays were developed to detect variants rs6717546 and rs4148324, and the linear formulas for each genotype of rs6717546 and rs4148324 were established. The method allowed to quantitatively determine each genotype and showed 100% accordant results against a panel of defined mixtures. A set of 24 template fragments containing variants rs6717546 or rs4148324 was tested to evaluate the method. Our results showed that allele frequency of each genotype was accurately quantified, with results comparable to those of conventional pyrosequencing. Furthermore, this method was capable of detecting alleles with frequencies as low as 3%, which was more sensitive than ∼5 to ∼7% level detected by conventional pyrosequencing. This method offers high sensitivity, reproducibility, and relatively low costs, and thus could provide a much‐needed approach for quantitative analysis of SNPs in clinical samples.